Burkitt non-Hodgkin lymphoma presenting with mental neuropathy ('numb chin' syndrome) in an HIV-positive patient. (May 2018) - Vora, N; Haryee, H; Dickson, JC; Miller, RF
Mental nerve neuropathy is usually due to local trauma or dental causes, but may be a manifestation of malignancy. A patient with virologically controlled human immunodeficiency virus (HIV) infection presented with a 'numb chin' on the background of long-standing night sweats, malaise and weight loss, worsening respiratory symptoms, and lymphadenopathy. Burkitt non-Hodgkin lymphoma was diagnosed from histology of a lymph node. Imaging (magnetic resonance imaging and 18 fluorodeoxyglucose [FDG]-positron emission tomography-computed tomography [PET-CT]) showed abnormal intracranial enhancement of the right mandibular nerve and extensive 18 FDG-avid lymphadenopathy above and below the diaphragm, focal lesions in the spleen and within the right mandible. The patient received chemotherapy and remains in clinical and radiological remission seven years later. This case highlights the need for clinicians to maintain a high index of suspicion for underlying malignancy when an HIV-infected patient presents with new onset of a 'numb chin'. Additionally, it demonstrates the importance of functional 18 FDG-PET-CT and neuroimaging in order to identify site(s) of pathology.